Near zero fluoroscopy cryoballoon catheter ablation in patients with atrial fibrillation using a novel dielectric imaging system. (25th November 2020) - Schillaci, V; Stabile, G; Arestia, A; Shopova, G; Agresta, A; Solimene, F
Abstract: Background: Fluoroscopy is commonly used in cryoballoon catheter ablation for pulmonary vein (PV) isolation procedures in patients with atrial fibrillation (AF). Purpose: The purpose of this study was to verify the feasibility of a new dielectric imaging system in reducing the radiation exposure during cryoballoon ablation in patients with AF. Methods: We enrolled 40 consecutive patients with paroxysmal AF: 20 patients underwent the procedure under fluoroscopy guidance before the new system introduction, while 20 patient underwent the procedure under fluoroscopy and a new dielectric imaging system guidance with its occlusion tool software. After transseptal access a detailed image reconstruction of left atrium and PVs was achieved with an octapolar circular mapping catheter and the cryoablation was performed with a cryoballoon catheter. Results: Total time of the procedure was comparable between the two groups (90.15±28.67 vs 80.77±17.17 using the dielectric imaging system, p=0.34), while fluoroscopy time was significantly lower in the group using the new dielectric imaging system (16.92±8.96 vs 5.54±2.06, p<0.01). Acute isolation was achieved in all PVs. No 30 days complication was observed. Conclusion: This is the first study that demonstrates the feasibility of a reduce fluoroscopy workflow using the novel dielectric imaging system in a cryoballoon procedure. Funding Acknowledgement: Type of funding source: None